OPTIMIZATION OF SHARIA BANK CUAN IN THE INDUSTRIAL ERA 4.0 - Alhamdi, Ridha; Sugianto, Sugianto; Siregar, Saparuddin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Is how to develop products and services to boost productivity and competitiveness in the economic and business industries. As for the opportunities owned by Islamic banking to develop products and services to face industry 4.0, namely, the first is qualified human resources, the second is technological sophistication, and the third is the products that society needs in facing the industrial revolution 4.0. The results of this study are that there are several opportunities and challenges faced by Islamic banks in Indonesia in facing the industrial revolution 4.0 in the scope of financial technology (fintech). the three products that society needs in facing the industrial revolution 4.0. The results of this study are that there are several opportunities and challenges faced by Islamic banks in Indonesia in facing the industrial revolution 4.0 in the scope of financial technology (fintech). the three products that society needs in facing the industrial revolution 4.0. The results of this study are that there are several opportunities and challenges faced by Islamic banks in Indonesia in facing the industrial revolution 4.0 in the scope of financial technology (fintech).